1999
DOI: 10.1111/j.1528-1157.1999.tb02088.x
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Pharmacokinetics of the New Antiepileptic Drugs

Abstract: Summary: Because pharmacokinetics is a major determinant of the magnitude and duration of pharmacologic response, understanding the kinetic properties of the new antiepileptic drugs (AEDs) is essential for the correct use of these compounds in clinical practice. After oral administration, absorption is rapid and relatively efficient for the new AEDs, the most notable exception being gabapentin, whose bioavailability decreases with increasing dosage. None of the new AEDs is extensively bound to plasma proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 66 publications
0
77
0
Order By: Relevance
“…Including the quantitative TBW covariate, LTG CL in the final model proposed was 0.039 L·h -1 ·kg -1 , which is higher than the values of approximately 0.021 to 0.035 L·h -1 ·kg -1 that were reported in PK studies evaluating small numbers of adult patients and healthy adult volunteers using standard approaches (2-stage methods with a 1-compartment model) [8][9][10]24] . Our study has shown a nonlinear increase of the CL and V d of LTG with an increase in total body weight.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Including the quantitative TBW covariate, LTG CL in the final model proposed was 0.039 L·h -1 ·kg -1 , which is higher than the values of approximately 0.021 to 0.035 L·h -1 ·kg -1 that were reported in PK studies evaluating small numbers of adult patients and healthy adult volunteers using standard approaches (2-stage methods with a 1-compartment model) [8][9][10]24] . Our study has shown a nonlinear increase of the CL and V d of LTG with an increase in total body weight.…”
Section: Discussionmentioning
confidence: 97%
“…Despite LTG's wide clinical use, standard npg dosage regimens continue to be used even though they may often be suboptimal because of the high variability found in CL values in the target population [7,10,[13][14][15][16][17][18] . This observation, together with previous studies that have established definable relationships between LTG blood concentrations and therapeutic and toxic effects [19][20][21] , justify TDM as an indicator of drug exposure for the individualization of LTG doses [4][5] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, medications that induce hepatic enzymes may decrease lamotrigine's half-life to 14-16 hours, and dosing must be adjusted accordingly. 10,15 Oral contraceptives decrease lamotrigine half-life, but as combined oral contraceptive monthly packs have seven days with no hormonal placebo pills, lamotrigine levels can rise by as much as 40%, leading to monthly flucutuations and causing side effects.…”
Section: Lamotriginementioning
confidence: 99%